DIRECTIONS OF PROBLEMATIC TEACHING TECHNOLOGY IN ENGINEERING SCIENCES AND PROBLEM-BUILDING TECHNOLOGY - Nurullaev Usmon Allakulovich (International Scientific and Current Research Conferences, 2023)
Today, students need to learn as much information as possible from various fields of science, as well as to develop the skills of independence and creative attitudes toward life. To that end, it is proposed to be based on methods that remind students of the study, end with "Discoveries," that is, they independently draw conclusions and solve some practical task.